Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1988
DOI: 10.1007/bf00401019
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol production and toxicity in suspension-cultured carrot cells and embryos

Abstract: The process of carrot (Daucus carota L.) somatic embryogenesis is highly sensitive to exogenously added ethanol, since 5 mM ethanol inhibits this process by 50%, whereas the growth of proliferating carrot cells is inhibited to the same extent by 20 mM ethanol. This is consistent with the fact that proliferating cultures produce ethanol and release it into the medium at concentrations up to 20 mM, whereas embryogenic culture medium contains less than 1 mM ethanol. Data are presented showing the influence of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…1 b). This response indicated a root oxygen deficiency in plants grown in the hypoxic media and the potential for alcoholic fermentation (Smith and ap Rees 1979;Keeley 1979;Perata et al 1988) (Fig. lb).…”
Section: Discussionmentioning
confidence: 95%
“…1 b). This response indicated a root oxygen deficiency in plants grown in the hypoxic media and the potential for alcoholic fermentation (Smith and ap Rees 1979;Keeley 1979;Perata et al 1988) (Fig. lb).…”
Section: Discussionmentioning
confidence: 95%
“…In 1971, McManmon and Crawford (13) suggested that the diversification of the end products of fermentive metabolism could explain flooding tolerance in some species. Jackson et al (9) questioned whether ethanol itself could be responsible for anoxic injuries, but we (17,18) later demonstrated that ethanol can be toxic to specific plant systems even at concentrations comparable to those commonly found in plant tissues subjected to oxygen deficit.…”
mentioning
confidence: 86%
“…As part of our work concerning ethanol toxicity to plants (2,(15)(16)(17)(18), we report the presence of reaction products of acetaldehyde with carrot cell proteins. We used an immunological approach, with the aim of verifying the presence of such conjugates in relation to the induction of injuries to ethanol-treated carrot cells.…”
mentioning
confidence: 99%
“…The process of carrot somatic embryogenesis is almost completely arrested by the addition of ethanol to the culture medium (Perata et al, 1988). The concentration of AA that inhibits cell growth is 40-fold lower than the concentration of ethanol that has a similar affect.…”
mentioning
confidence: 99%